The Drosophila MCPH1-B isoform is a substrate of the APCCdh1 E3 ubiquitin ligase complex - Sarah G. Hainline; Jamie L. Rickmyre; Leif R. Neitzel; Laura A. Lee; Ethan Lee (Biology Open, 2014)
The Anaphase-Promoting Complex (APC) is a multi-subunit E3 ubiquitin ligase that coordinates progression through the cell cycle by temporally and spatially promoting the degradation of key proteins. Many of these targeted proteins have been shown to play important roles in regulating orderly progression through the cell cycle. Using a previously described Drosophila in vitro expression cloning approach, we screened for new substrates of the APC in Xenopus egg extract and identified Drosophila MCPH1 (dMCPH1), a protein encoded by the homolog of a causative gene for autosomal recessive primary microcephaly in humans. The dMCPH1-B splice form, but not the dMCPH1-C splice form, undergoes robust degradation in Xenopus interphase egg extract in a Cdh1-dependent manner. Degradation of dMCPH1-B is controlled by an N-terminal destruction box (D-box) motif as its deletion or mutation blocks dMCPH1-B degradation. dMCPH1 levels are increased in Drosophila morula (APC2) mutant embryos, consistent with dMCPH1 being an APC substrate in vivo. Using a purified, reconstituted system, we show that dMCPH1-B is ubiquitinated by APCCdh1, indicating that the effect of APC on dMCPH1-B ubiquitination and degradation is direct. Full-length human MCPH1 (hMCPH1) has been predicted to be an APC substrate based on its interaction with the APC subunit Cdc27. We were not able to detect changes in hMCPH1 levels during the cell cycle in cultured human cells. Overexpression of hMCPH1 (or dMCPH1-B) in developing Xenopus embryos, however, disrupts cell division, suggesting that proper regulation of hMCPH1 and dMCPH1-B activity plays a critical role in proper cell-cycle progression.